Application of Robotics in Large-Scale Agriculture in Australia - Kuhtreiber Emma; Willem Hostetter; Wolfe Maya (Techno Agriculturae Studium of Research, 2024)
The agricultural sector in Australia faces challenges related to labor shortages, high operational costs, and the need for increased efficiency and productivity. Robotics technology offers promising solutions to these challenges by automating various farming tasks, enhancing efficiency, and reducing reliance on manual labor. This study explores the application of robotics in large-scale agriculture in Australia, focusing on its impact on productivity, cost efficiency, and sustainability. The primary aim of this research is to evaluate the effectiveness of robotic technology in improving agricultural practices on large-scale farms in Australia. The study assesses how robotics can enhance productivity, reduce operational costs, and promote sustainable farming practices. A mixed-methods approach was employed, combining quantitative data from field experiments and qualitative insights from interviews with farmers and agricultural experts. Field experiments involved deploying robotic systems for planting, harvesting, and monitoring crop health. Data on productivity, cost savings, and environmental impact were collected and analyzed. Interviews with farmers and experts provided additional insights into the practical benefits and challenges of implementing robotic technology in agriculture. The findings indicate that using robotics in large-scale agriculture significantly increases productivity and reduces operational costs. Robotic systems improved planting and harvesting efficiency by 40% and reduced labor costs by 30%. Environmental benefits were also observed, with more precise application of inputs leading to reduced waste and lower chemical usage. Farmers reported improved crop monitoring and management capabilities, contributing to better overall farm management. The application of robotics in large-scale agriculture in Australia offers substantial productivity, cost efficiency, and sustainability benefits. The study highlights the potential of robotic technology to address labor shortages and operational challenges in the agricultural sector. Further research and investment in robotics are recommended to optimize their use and fully realize their potential in transforming large-scale farming practices.